Jack Reacher. Never go back [videorecording (Blu-Ray + DVD)] - Cruise, Tom, 1962-; Zwick, Edward; Wenk, Richard; Herskovitz, Marshall; Smulders, Cobie, 1982-; Hodge, Aldis; Yarosh, Danika; Heusinger, Patrick; McCallany, Holt; Knepper, Robert, 1959-; Jackman, Henry (Henry Pryce); Wood, Oliver (Cinematographer); et al. (Paramount, 2017)
While on the run trying to clear himself of murder and a former colleague of treason, itinerant former U.S. Army Major Jack Reacher discovers both a conspiracy involving the murder of soldier and a potential secret from his past that could change his life forever.